2013
DOI: 10.1007/s11356-013-2442-y
|View full text |Cite
|
Sign up to set email alerts
|

Children and elders exposure assessment to particle-bound polycyclic aromatic hydrocarbons (PAHs) in the city of Rome, Italy

Abstract: It has been amply demonstrated that exposure to fine particulate matter, containing polycyclic aromatic hydrocarbons (PAHs), may have adverse effects on human health, affecting especially the respiratory and cardiovascular systems. Among population, school-age children and elders present particular susceptibilities and unique exposures to environmental factors. The study presented in this paper belongs to the Project EXPAH, founded by the European (EU) LIFE+ instrument, and consists of the personal monitoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 26 publications
3
13
0
Order By: Relevance
“…The reported levels of all studies available in literature are summarized in Table 3. In general, the levels of PM 2.5-bound PAHs in this study were similar to those reported from elementary schools in Rome during winter season (Gatto et al, 2013), whereas no information was found on PM 1 -bound PAHs in indoor air of schools and/or preschools. Concerning gaseous PAHs, the most similar range of concentrations was observed in primary schools in Lithuania (Krugly et al, 2014).…”
Section: Indoor Pahssupporting
confidence: 78%
“…The reported levels of all studies available in literature are summarized in Table 3. In general, the levels of PM 2.5-bound PAHs in this study were similar to those reported from elementary schools in Rome during winter season (Gatto et al, 2013), whereas no information was found on PM 1 -bound PAHs in indoor air of schools and/or preschools. Concerning gaseous PAHs, the most similar range of concentrations was observed in primary schools in Lithuania (Krugly et al, 2014).…”
Section: Indoor Pahssupporting
confidence: 78%
“…With the exception to S2 (range: 33-63 ng m −3 ;meanof48ngm −3 ), mean concentrations of PM 2.5 -bound PAHs in outdoor air of the Portuguese primary schools (6.4 ng m −3 at S10-16 ng m −3 at S8) were similar to the levels reported in winter for ambient air in Rome (4.5-18 ng m −3 ; obtained from fixed stations of the environmental monitoring network; Gatto et al, 2013) or for outdoors of schools in Rome (6.3-9.5 ng m −3 ; Romagnoli et al, 2014). For warmer seasons (0.21-1.3 ng m −3 in ambient air by Gatto et al, 2013;0.42-1.7 ng m −3 reported by Romagnoli et al, 2014) and in other European countries (Lithuania; 41-120 ng m −3 ; Krugly et al, 2014) considerably different levels of particulate-bound PAHs were observed. Although there was no specific emission source that could justify the increased levels of ambient PAHs at S2, the respective sampling was conducted during a period with harsh meteorological conditions (causing atmospheric inversion), which could lead in overall elevated levels of pollutants in the atmosphere.…”
Section: S1supporting
confidence: 76%
“…During the past decade, many studies were conducted to assess indoor air quality, mainly in school environments. A large number of indoor air pollutants were measured, including sulfur dioxide (SO 2 ), nitrogen oxides (NO x ), ozone (O 3 ), carbon mon- and dioxide (CO and CO 2 ), volatile organic compounds (VOCs), bioaerosols, PM, and PAHs, and selected heavy metals, including mercury (Mendell and Heath 2005 ; Stranger et al 2008 ; Demirel et al 2014 ; Rivas et al 2014 ; Gatto et al 2014 ; Mainka and Zajusz-Zubek 2015 ; Tofful and Perrino 2015 ; Majewski et al 2016 ), but very few authors reported results on indoor air quality in kindergartens or day care centers (Wichmann et al 2010 ; Branco et al 2014 ; Mainka and Zajusz-Zubek 2015 ). Mutagenicity of indoor particulate matter evaluated using TA98 and YG1024 strains was examined only in places of residence in Japan, Thailand, and China (Zhou et al 2000 ; Takagi et al 2002 ; Chunram et al 2007 ).…”
Section: Introductionmentioning
confidence: 99%